Kimbanguism, Garveyism, and Rebellious Rumor Making in Post–World War I Africa - Ewing, Adam (Souls, 2018)
In the spring of 1921, a young Kongo prophet named Simon Kimbangu launched a revival that won thousands of followers and posed a growing threat to Belgian rule in the Congo. This article examines the dynamic confluence of the Kimbanguist revival and the spread of Garveyism along the west coast of Africa. Scholarly treatments of Kimbanguism have not satisfactorily explained this connection, in large part because Garveyism has been traditionally miscast as an American-centered doctrine of immediate liberation rather than a malleable and portable diasporic movement that acquired a uniquely African cast as a result of its spread through the subcontinent. In the Belgian Congo, Garveyism provided an organizational spark that aided the emergence of Kimbangu's church. Perhaps more consequentially, the spread of Garveyism through the region facilitated the emergence of rumors that conditioned the manner in which both Africans and Europeans perceived and responded to the revival. Viewing Garveyism from this perspective helps us understand why it was such a vibrant politics during the interwar period. It also suggests the broader utility of diasporic identifications and ideas as potentially emancipatory materials for local politics making.
Paid
Keywords: Africa; Belgian Congo; Diaspora; Garveyism; Kimbanguism; Marcus Garvey; Universal Negro Improvement Association; rumor